SYNTHESIS OF ALUMINIUM-SILICEOUS ALLOYS BY MEANS OF SILICON DIRECT REVIVIFICATION USING OF ALUMINA-MATRIX COMPOSITION ALLOYS - A. V. Arabej; I. V. Rafalskij (Литьë и металлургия, 2011)
The new resource-saving methods of synthesis of aluminium alloys with usage of alumomatrix compositions ligatures are given.